Optical Frequency Comb Generation Based on Dual-Polarization IQ Modulator Shared by Two Polarization-Orthogonal Recirculating Frequency Shifting Loops - Jianping Li; Huatao Ma; Zhaohui Li; Xiaoguang Zhang (IEEE Photonics Journal)
A novel optical frequency comb generator (OFCG) based on a dual-polarization IQ modulator shared by two polarization-orthogonal recirculating frequency shifting (RFS) loops has been proposed. The states of polarization of two optical subcombs output from the respective loops are kept orthogonal in the proposed scheme. More than 80 carriers, whose carrier-to-noise ratio (CNR) can be further improved with better conditions, have been demonstrated experimentally. Meanwhile, the number and frequency spacing of the carriers of both the two optical subcombs can be easily tuned due to the unique feature of flexible controls, which is different from the previous dual-RFS-loop-based OFCG in which the carrier frequency spacing must be kept fixed. Based on the theoretical and experimental results, the proposed scheme has the advantages of good feasibility, tunability, and flexibility, which can find the potential applications in various fields.